LO103: Trauma Resuscitation Using in-situ Simulation Team Training (TRUST): using risk-informed simulation for team performance and human factors evaluation. (2nd June 2016) - Gray, A.; Hicks, C.; White, K.; McGowan, M.; Chow, R.; Campbell, D.; Petrosoniak, A.
Abstract : Introduction / Innovation Concept: Trauma resuscitation requires a multidisciplinary team to perform at a high level within a dynamic, high-stakes environment. The unpredictable nature of trauma care increases the possibility for errors, often from underlying latent safety threats (LSTs). In-situ simulation (ISS) is a point-of-care training strategy that occurs within the patient care environment involving the actual healthcare team and provides a novel approach to team training and LST identification. Using ISS, critical events can be recreated providing an opportunity to explore and learn from past challenges. We developed and piloted a risk-informed, multidisciplinary ISS trauma training program to assess teamwork performance and identify LSTs within the trauma care environment.Methods: A comprehensive process was initiated to gain support from all stakeholders within the trauma program. Simulation cases were derived from a review of adverse events and unexpected deaths. Human factors experts aided with the integration of system- and process-related elements into the case design. ISS sessions involved all trauma team members. Debriefing after each session facilitated a team-based discussion and an opportunity for reflective practice and video recording was used for teamwork evaluation and process mapping.Curriculum, Tool, or Material: We conducted monthly, unannounced, multidisciplinary, high-fidelity ISS scenarios at a Canadian Level 1 trauma centre. The trauma team was activated by the usual notification process and care provided in the same manner as an actual trauma patient. A semi-structured debriefing followed each session with a focus on team performance and LST identification. Teamwork was measured using a previously validated tool, the Clinical Teamwork Scale. Findings were used to inform discussion at multidisciplinary trauma rounds as part of an iterative process of evaluation and implementation.Conclusion: This multidisciplinary ISS trauma training program offers a novel approach to team performance evaluation and LST identification. Using risk-informed scenarios combined with human factors analysis we are able identify knowledge and technical skill proficiency gaps, LSTs and integrate formative team assessment. An iterative process beginning with ISS followed by multidisciplinary rounds provides a robust framework for system-based changes to improve team performance and overall patient care.